A BALANCE POINT BETWEEN THE SCIENCE OF NUTRITION AND "FAT STUDIES" - Andreia Araujo Lima Torres (Universidade do Estado do Rio de Janeiro, 2016)
The concern for physical appearance is great in the West. However, the search for such ideals can trigger body image dissatisfaction, eating disorders, body image disorders, stereotypes and negative attitudes towards individuals outside the standard valued by the media. Groups linked to sociology, gender studies and feminist activism have joined the debate that forms an interdisciplinary field called fat studies. The field shifts the focus from the pathophysiological aspects associated with body fatness to the situation of these people in society, and harshly criticizes the biomedical model and its ineffectiveness in treating obesity. On the other hand, health researchers are concerned about defending that health would be possible with any weight or body fat percentage by simply adopting a healthier lifestyle. This article explores the subject and aims for an approximation between the research fields. DOI: 10.12957/demetra.2016.25885